Lag på lag av hjemsøkelse: – Effekten av Ghosting i Jack Thornes "The Motive and the Cue" - Maagerø, Lars Harald (Teatervitenskapelige studier, 2025)
Over 20 years has passed since Marvin Carlson defined the concept of ghosting in the seminal book The Haunted Stage. Carlson suggests that the theatre is obsessed with ghosts, both in many of the actual stories it tells, but also in the ways stories, people, spaces and production modes are constantly reused and recycled. This article discusses a production in which ghosting was particularly important: The 2023 National Theatre Production of Jack Thorne’s play The Motive and the Cue, a play about the rehearsal process for the famous 1964 production of Hamlet directed by John Gielgud and starring Richard Burton. The article discusses the intricate ways in which this production was ghosted both by Shakespeare’s Hamlet, but also by British theatre history and theatre traditions more generally. Carlson’s term is used together with Chantal Mouffe’s ideas of critical art to discuss the effects of ghosting in the production, and to ultimately argue that the production firmly contributed to the dominant consensus in British theatre.